Фактор-группы групп некоторых классов - Черников, Н.С.; Требенко, Д.Я. (Український математичний журнал, 2000)
Для довільного многовиду X груп і довільного класу Y груп, що замкнений за фактор-групами, доведено, що фактор-група G/N групи G має інваріантну систему X і Y -факторами (відповідно, апроксимується Y -групами) у випадку, коли G має інваріантну систему X і Y-факторами (відповідно, апроксимується Y-групами) і N∈X де (відповідно, N∈X максимальною інваріантною X-підгрупою групи G). For an arbitrary variety X of groups and an arbitrary class Y of groups that is closed on quotient groups, we prove that a quotient group G/N of the group G possesses an invariant system with X - and Y -factors (respectively, is a residually Y -group) if G possesses an invariant system with X - and Y -factors (respectively, is a residually Y -group) and N ∈ X (respectively, N is a maximal invariant X -subgroup of the group G).